(Re)Valuing Local Sheep Wool in the Czech and Slovak Republic: Some Examples of the Border between Arts and Crafts - Špinková Tereza (European Countryside)
This paper explores the devaluation and recent revitalization efforts of local sheep wool in the Czech and Slovak Republic, where wool has become a waste due to economic and structural changes in the agricultural and textile sector especially after 1992. Through an interdisciplinary and (post)qualitative approach combining interviews, observation, and theoretical insights from posthumanism, ecofeminism and Actor-Network Theory the study analyzes initiatives that bridge eco sheep farming with arts and crafts. Through three case studies – the Kubák Weaving mill, the multispecies art practice of Kateřina Žák Konvalinová, and the Slovak initiative Naša Vlna – the article analyzes how human, and nonhuman actors collaborate to build alternative wool communities, economies and values. The research examines wool’s potential as a transformative material within ecological, social, and cultural contexts. This study aims to uncover strategies that are still in the infancy, but they reestablish wool’s value in sustainable production chains, promote community building, and foster innovative practices.